Analisis Yuridis Tanggung Jawab Hukum atas Kekerasan yang Dilakukan oleh Oknum Kepolisian - Akuna, Sandrawati; Ismail, Dian Ekawaty; Mustika, Waode (Journal Evidence Of Law, 2025)
This article aims to analyze the legal responsibility for violence committed by police officers, with a focus on cases of wrongful arrest and violence in Gorontalo. This study was motivated by the increasing number of cases of violence by law enforcement officials, which not only violate human rights and the principles of the rule of law but also undermine public trust in the police institution. The method used is normative legal research, with a legislative and conceptual approach. The analysis was conducted on primary legal materials such as laws, government regulations, and implementing regulations, as well as secondary legal materials such as literature, journals, and legal expert opinions. The results of the study indicate that violence by police officers, particularly in cases of wrongful arrest, constitutes a serious violation of the right to freedom and fair treatment before the law. The legal responsibilities that can be imposed include criminal, civil, administrative, and disciplinary liability. Criminal sanctions are imposed if there is evidence of intent or gross negligence, while civil sanctions provide victims with the opportunity to seek compensation. Administrative and disciplinary sanctions, such as reprimands or dismissal, are also important to maintain the integrity of the police institution. Informal resolution through restorative justice mechanisms should not eliminate legal accountability and the victim's right to redress. This study emphasizes the importance of strengthening complaint mechanisms, external oversight, and legal and institutional reforms to ensure the protection of victims' rights and the accountability of police officers in practice.